Ureteral Strangulation by Fibrosis: A Cold Case Report of Ormand's Disease - Amarpreet Sandhu; Leslea Brickner; Mark Chen (Case Reports in Nephrology)
Retroperitoneal fibrosis or Ormand's disease is rare in incidence and clinically elusive to diagnosis until obstructive uropathy clinically manifests by the mechanism of ureteral fibrotic strangulation and acute renal failure. We encountered a 50-year-old woman with months of nonspecific abdominal pain and presented with signs and symptoms of acute renal failure. Laboratory data was significant for blood urea nitrogen 47 mg/dL and creatinine of 8.47 mg/dL. Renal ultrasound revealed bilateral hydronephrosis and an abdominal computed tomogram confirmed an abnormal soft tissue retroperitoneal confluence that encased the pelvic vessels. Urologic consultation was requested and bilateral ureteral stents were placed with relief of her obstructive uropathy. Five days after ureteral stenting her creatinine dropped to 1.64 mg/dL. One month later patient underwent ureterolysis with biopsy showing fibroblast proliferation consistent with acute and chronic inflammation. By ruling out infections and malignancy, the final diagnosis was made to be idiopathic retroperitoneal fibrosis.